Agency and Architecture: How to Be Critical? (Scott Lash and Antoine Picon, in conversation with Kenny Cupers and Isabelle Doucet. Comments by Margaret Crawford) - Scott Lash; Antoine Picon; Margaret Crawford (Footprint)
Agency is a notion that brings together a variety of concerns that currently echo in diverse segments of the architectural debate. This article, in the form of a conversation, addresses this multifarious notion and attempts to bring to the fore points of intersection between agency-related concerns too often perceived as disconnected. The article has been assembled out of separate interviews with three prominent scholars who have, from different fields, made particular contributions to this theme: Antoine Picon, historian of architecture and technology; Scott Lash, professor of sociology and cultural studies; and Margaret Crawford, professor in architecture and urban studies. This conversation interrogates agency theoretically, and does so through three major questions. One question relates to agency’s binary coupling with structure, perhaps one of the most central concepts in the understanding of modern society. Secondly, because agency is intimately linked to the idea of ‘other’ possible actions and futures, it assumes intentionality and criticality, both of which resonate strongly in the architectural debate. Finally, in order to understand agency better within the specific context of architecture, the article addresses the condition of the architectural object and its relation to the individual and the social.